The Role of Self Leadership for Employees in Implementing Work From Home (WFH) During the COVID 19 Pandemic - Bandi, Anisa Arizona (Technium Social Sciences Journal, 2022)
This study aims at answering the questions of what obstacles experienced by employees who have to carry out Work From Home (WFH) and how employees apply Self Leadership in implementing WFH. This study is a qualitative research with a phenomenological approach. Data was collected through semi-structured interviews and in a fluid atmosphere. In this study, interviews were conducted with 20 employees who had to work with the WFH system to obtain data whether employees were familiar with Self Leadership and whether they had implemented it during WFH. The researcher also conducted interviews with 2 HRD heads to see if every leader has already understood how to motivate their subordinates to have self-leadership. This study proves that self-leadership is very important for everyone who runs WFH. The WFH system where people have to work independently requires everyone to be able to organize themselves, motivate themselves and discipline themselves so that the tasks or work entrusted to them can be completed properly.